Generic names for the Mbira. (A Contribution to Hugh Traceys article A Case for the name Mbira) - Kubik, Gerhard (International Library of African Music, 1964)
During three research trips in fourteen countries of Sub-Saharan Africa I have quite often met and recorded this instrument. Incited through Hugh Traceys extensive list I should like to provide some names from the regions I have visited, as a supplement. After that, we shall try to see what conclusions might be drawn from the various names given in the combined lists
Keywords: Africa; Musical instruments; Ethnomusicology; Mbira; Mbira music; African Music; Mbira (Instrument)